Distributed hydrologic modeling using GIS - Vieux, Baxter E. (Kluwer, 2001)
This book is generally concerned with surface runoff and flood periods, the conceptions and methods, as well as the method of utilizing GIS for distributed models, are remakably useful. Careful study of this excellent book will help achieve understanding of GIS-based distributed modelling, and it is highly recommended to students, teachers, researchers, and engineers involved in hydrology, water resources, and environmental Sciences